ANALISIS KOMPARATIF REGULASI DAN FATWA DALAM SCREENING SAHAM SYARIAH: STUDI INVESTASI ISLAMI ANTARA INDONESIA DAN MALAYSIA - Syamsul Wathoni; Hafisuddin Aritonang; Zulhaji Ismail; Khaerul Muttaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to comparatively analyze the relationship between religious fatwas and state regulations in the Sharia stock screening system in Indonesia and Malaysia. Using a qualitative approach and juridical-normative method, this research is supported by three theoretical frameworks: legal pluralism, normative authority, and comparative law. The results show that Indonesia applies a dualistic model where the DSN-MUI fatwa serves as a moral reference, which is then partially accommodated by OJK regulations. In contrast, Malaysia adopts an integrative approach through the SAC-SC, which functions as an official state institution with legally binding authority. Significant differences are also found in the financial indicators, where Malaysia sets stricter debt and non-halal income ratio limits consistent with international standards such as AAOIFI. These findings reflect the different epistemological and institutional approaches to internalizing Shariah principles into the capital market system. This research contributes to the study of Islamic economic law by offering a new understanding of the ideal form of relationship between regulation and fatwa in supporting the integrity and legitimacy of Islamic capital markets.